2001
DOI: 10.1063/1.1374584
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of electron beams produced by ultrashort (30 fs) laser pulses

Abstract: International audienceDetailed measurements of electron spectra and charges from the interaction of 10 Hz, 600 mJ laser pulses in the relativistic regime with a gas jet have been done over a wide range of intensities (10^18–2×10^19 W/cm^2) and electron densities (1.5×10^18–1.5×10^20 cm^−3), from the “classical laser wakefield regime” to the “self-modulated laser wakefield” regime. In the best case the maximum electron energy reaches 70 MeV. It increases at lower electron densities and higher laser intensities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 22 publications
4
82
2
Order By: Relevance
“…The quasistatic nature of the bulk plasma response makes it possible to elucidate the physics of self-injection using a conceptually simple and computationally efficient toolbox: a fully relativistic 3D particle tracking module 24,39 built into the cylindrically symmetric time-averaged quasistatic PIC code WAKE. 38 WAKE models the laser pulse propagation using an extended paraxial solver.…”
Section: Scenarios Of Self-injection In the Blowout Regimementioning
confidence: 99%
See 1 more Smart Citation
“…The quasistatic nature of the bulk plasma response makes it possible to elucidate the physics of self-injection using a conceptually simple and computationally efficient toolbox: a fully relativistic 3D particle tracking module 24,39 built into the cylindrically symmetric time-averaged quasistatic PIC code WAKE. 38 WAKE models the laser pulse propagation using an extended paraxial solver.…”
Section: Scenarios Of Self-injection In the Blowout Regimementioning
confidence: 99%
“…In particular, it takes into account the interaction of test electrons with the nonaveraged, linearly polarized laser field with nonparaxial corrections. 39,42 To capture the laser pulse interaction with nonquasistatic background electrons (and thus to model self-injection into nonstationary quasistatic wake fields), a group of quiescent test electrons is placed before the laser pulse at each time step. In this way, electron self-injection associated with bubble and driver evolution is separated from the effects brought about by the collective fields of the trapped electron bunch, i.e., from effects due to beam loading.…”
Section: Scenarios Of Self-injection In the Blowout Regimementioning
confidence: 99%
“…At larger densities, the x-ray signal drops down and a plateau is reached. For these experimental conditions, the laser must first be modulated to create high amplitude plasma waves [20] and much higher laser intensity is needed.…”
Section: Fig 4 (Color Online)mentioning
confidence: 99%
“…At present, thermionic and photoemission based electron sources are widely used [25]; however, plasma based electron sources are an active topic of research due to their potential to produce high current and low emittance electron bunches [67,23,17,3,40,44,49,16]. Recently it was shown that PWFAs, operated in the nonlinear bubble regime, can trap electrons that are released by ionization inside the plasma wake [58] and accelerate them to high energies.…”
Section: Introductionmentioning
confidence: 99%